Penggerombolan Data Panel Perusahaan Sektor Barang Konsumsi - Radinda Putri Maha Dewi; Pika Silvianti; Septian Rahardiantoro (Xplore: Journal of Statistics, 2020)
The identification of the cluster of consumer goods sector companies is enough important study to examine the characteristics of the company based on its marketing management factors. This study seeks to cluster 23 consumer goods sector companies based on 4 marketing management factors, which are production costs, promotion costs, distribution costs, and sales value in 2012-2016. There are two parts of clustering that are carried out, the clustering of consumer goods sector companies based on the time series pattern for each marketing management factor with the ward method, and clustering of consumer goods sector companies using multivariate panel data using the k-means method. The results of the clustering for each marketing management factor using the ward method produced 2 groups in each factor, with cluster 2 having an average of each factor greater than group 1. The companies found in cluster 2 were PT Indofood CBP Sukses Makmur, PT Indofood Sukses Makmur, PT Mayora Indah, PT Unilever Indonesia Tbk, PT Handjaya Mandala Sampoerna Tbk, International Investama Tbk, PT Kalbe Farma Tbk, and PT Tempo Scan Pacific Tbk. On the other hand, clustering of multivariate panel data produced 6 groups where group 5Â  is the cluster with the highest average on each factor. Group 5 consists of PT Indofood Sukses Makmur and PT Handjaya Mandala Sampoerna Tbk. The company with the highest value in multivariate panel data is also found in the results of the cluster with the highest value for each marketing management factor.